2014
DOI: 10.1111/cmi.12379
|View full text |Cite
|
Sign up to set email alerts
|

An AIL family protein promotes type three secretion system-1-independent invasion and pathogenesis ofSalmonella entericaserovar Typhi

Abstract: SummaryAdhesion and invasion of Intestinal Epithelial Cells (IECs) are critical for the pathogenesis of Salmonella Typhi, the aetiological agent of human typhoid fever. While type three secretion system-1 (T3SS-1) is a major invasion apparatus of Salmonella, independent invasion mechanisms were described for non-typhoidal Salmonellae. Here, we show that T2942, an AIL-like protein of S. Typhi Ty2 strain, is required for adhesion and invasion of cultured IECs. That invasion was T3SS-1 independent was proved by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…This assay was done as reported previously (Chowdhury, Mandal, Ta, & Das, 2015). Briefly, HT-29 or Caco-2 cells were infected as described above and incubated at 37°C for 1 hr.…”
Section: Invasion Assaymentioning
confidence: 99%
“…This assay was done as reported previously (Chowdhury, Mandal, Ta, & Das, 2015). Briefly, HT-29 or Caco-2 cells were infected as described above and incubated at 37°C for 1 hr.…”
Section: Invasion Assaymentioning
confidence: 99%
“…Binding to Met for the 20mer peptide was comparable with that of rSTIV, whereas other peptides displayed higher K d values, suggesting less efficient interaction (Figure c1,c2). To further validate the above results, coimmunoprecipitation experiments were performed using antiserum (rabbit antiserum or RAS) against STIV from HT‐29 cell lysates pretreated with the individual peptides (Chowdhury et al, ). Immunoblots showed the presence of Met in the samples treated with STIV and the 20mer peptide, but not with the other peptides (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…These results were in agreement with our previous findings that showed adhesion of S . Typhi to laminin and fibronectin using STIV (Chowdhury et al, ) and suggested that STIV‐mediated invasion was strictly Met dependent. Similar results were obtained in epithelial cell lines such as Caco‐2 and HeLa cells, excluding cell line specificity of invasion (Figure S3B1‐4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations